Crustal architecture of the oblique-slip conjugate margins of George V Land and southeast Australia - Stagg, HMJ; Anya Reading (2007)
A conceptual, lithospheric-scale cross-section of the conjugate, oblique-slip margins of George V Land, East Antarctica, and southeast Australia (Otway Basin) has been constructed based on the integration of seismic and sample data. This cross-section is characterised by asymmetry in width and thickness, and depth-dependent crustal extension at breakup in the latest Maastrichtian. The broad Antarctic margin (~360 km apparent rift width) developed on thick crust (~42 km) of the Antarctic craton, whereas the narrow Otway margin (~220 km) developed on the thinner crust (~31 km) of the Ross–Delamerian Orogen. The shallow basement (velocities ~5.5 km.s -1 ) and the deep continental crust (velocities >6.4 km.s -1 ) appear to be largely absent across the central rift, while the mid-crustal, probably granitic layer (velocities ~6 km.s -1 ) is preserved. Comparison with published numerical models suggests that the shallow basement and deep crust may have been removed by simple shear, whereas the mid-crust has been ductilely deformed.